Twentieth Century Housewives and The Sexual Contract - Thompson, Sharon (feminists@law, 2018)
“If a wife has a right to the money she can save from her housekeeping allowance, she might let her husband go short of food while she builds up a banking account. She might serve him up corned beef instead of roast beef for dinner.” These are the words of Goddard LJ in Blackwell v Blackwell [1943] 2 All ER 579, where it was held that Mrs Blackwell’s savings of one hundred pounds ten shillings in the Oxford and District Co-operative Society were the property of her husband, from whom Mrs Blackwell had been separated for two years. Protection of the husband’s roast beef might have been secured, but the consequences for Mrs Blackwell were severe. Writing in 1967, Lady Summerskill described her as ‘helpless and hopeless, a victim of a legal system which still in the twentieth century treats the wife as a chattel of her husband’. In this paper, I argue that The Sexual Contract enriches our understanding of the lived experiences of twentieth century housewives like Mrs Blackwell by looking to the root causes of their oppression and finding them in the sexual contract underpinning marriage. The Sexual Contract also highlights the shortcomings of ‘conjectural histories’ and the importance of paying attention to the ‘missing half of the story’. This emphasises the need for a feminist history of family law, to appreciate the forgotten campaigns of pressure groups that sought to change the law affecting married women. Drawing on my forthcoming SLSA funded research, I take the Married Women’s Association as my focus. This group financed Mrs Blackwell’s unsuccessful appeal in 1943 and continued to campaign for legal reform of wives’ right to housekeeping money. Twenty years later, Lady Summerskill’s Married Women’s Property Bill gained Royal Assent (becoming the Married Women’s Property Act 1964), and provided that money given by a husband to his wife for housekeeping was to be held by husband and wife in equal shares. Yet as this paper explores, the story behind this short piece of legislation is often ignored, and Carole Pateman’s work helps us understand why. Paying attention to the role of the sexual contract in family law history requires a rewriting of orthodox history that does not forget women’s struggles for legal equality. Indeed, to properly understand why the law affecting married women is so different now, it is imperative that the Married Women’s Association’s hard-fought campaigns are not overlooked. While their campaigns might not have always led directly to reform, this group was an example of feminist activism in the mid-twentieth century that emphasised the inequity of the current law and created pressure for change.